2010
DOI: 10.1111/j.1759-1961.2010.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Theiler’s murine encephalomyelitis virus‐induced disease

Raymond P. Roos

Abstract: Theiler’s murine encephalomyelitis virus (TMEV) is a member of the Cardiovirus genus of the Picornaviridae family. Interest in TMEV is at least partly related to the fact that the Daniels (DA) strain and other members of Theiler’s original (TO) subgroup induce an inflammatory demyelinating disease in which the virus persists for the life of the mouse. This disease resembles multiple sclerosis because of the similar pathology and because the immune system seems to play an important role in both. The present rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 61 publications
(96 reference statements)
0
24
0
Order By: Relevance
“…Although various studies using recombinant viruses between GDVII and DA (or BeAn) strains demonstrated that capsid proteins, especially VP1 and VP2, are important for virus persistence and demyelination (14,23), the precise localization of the region responsible for those biological activities remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although various studies using recombinant viruses between GDVII and DA (or BeAn) strains demonstrated that capsid proteins, especially VP1 and VP2, are important for virus persistence and demyelination (14,23), the precise localization of the region responsible for those biological activities remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The TMEV genome is a single-stranded RNA molecule and translated as a long precursor polyprotein to yield 12 viral proteins by autoproteolytic cleavage (23). Two subgroup strains of TMEV have a sequence identity of approximately 95% at the amino acid level.…”
mentioning
confidence: 99%
“…Infected mice show progressive flaccid paralysis, and almost all infected mice die within 2 weeks. Neither virus persistence nor demyelination is observed in the few surviving mice (4,29,54). On the other hand, TO subgroup strains cause a milder encephalomyelitis 1 to 2 weeks postinoculation (p.i.).…”
Section: Safv-related Virusesmentioning
confidence: 99%
“…The capsid proteins, especially VP1 and VP2, were found important for some of the biological activities (29). In addition to these structural proteins, the two nonstructural viral proteins, L and L*, play an important role in TMEV disease pathogenesis (4,29,54).…”
Section: Safv-related Virusesmentioning
confidence: 99%
“…Theiler's murine encephalomyelitis virus (TMEV), or Theiler's virus, is a neurotropic picornavirus responsible for either acute or persistent and demyelinating infections of the mouse central nervous system (CNS) (3). The L* protein encoded by this virus is the sole protein encoded by an alternative ORF within the picornavirus family (19). L* was found to play an important role in the establishment of persistent CNS infections by TMEV (4,7,25).…”
mentioning
confidence: 99%